THE CINEMATIC OTHERING OF SITTING BULL IN THE ADAPTATION OF BURY MY HEART AT WOUNDED KNEE - Nurcahyo, Rachmat; Hapsarani, Dhita; Budianta, Melani; Kristianto, Bayu (International Review of Humanities Studies, 2023)
The marginalization of particular groups or people as a result of the idea that one group or person is better than another is known as the "othering" process. This article discusses how a film adaptation of Dee Alexander Brown’s book on Native American history, Bury My Heart at Wounded Knee (BMHWK) performs this act of othering. First of all, it is done by negatively portraying the heroic figure in the book. Sitting Bull, a Teton Dakota Chief who united the Sioux tribes in North America, the Great Plains, in mid 19th century is reduced in the film into a weak figure. The Native American chief is overshadowed by White figures like Elaine Goodale and Senator Henry Dawes. In the film adaptation, the social hierarchy-building process, which put the Whites on top, educated natives in the middle, and the rest of Native American population in the bottom, serves as a vehicle for a further process of othering. The film represents Native Americans as people who need to be governed and who can only survive if they abide by White people's laws.